Two new species and records of Stenochironomus Kieffer from Brazilian Amazon region, with description of immature stages (Diptera: Chironomidae) - Reis, Emiliano De Angelis; Filho, Arlindo Serpa; Ferreira-Keppler, Ruth L. (Zootaxa, 2013)
Two new species of Stenochironomus Kieffer, 1919 are described in Brazil. New records of Stenochironomus nudipupa Borkent, 1984 and S. gladius Borkent, 1984 from Brazil, new data on geographical distribution of S. jubatus Borkent, 1984 and S. triannulatus Borkent, 1984 from the State of Roraima, and S. bacrionis Borkent, 1984 recorded from the State of Amazonas, as well as emended descriptions of immature stages of S. triannulatus Borkent, 1984 and S. reissi Borkent, 1984 are also presented.